Mechanisms by which phytogenic extracts enhance livestock reproductive health: current insights and future directions - Adetunji, Adedeji O.; Price, Jacqueline; Owusu, Henrietta; Adewale, Esiosa F.; Adesina, Precious Adedayo; Saliu, Tolulope Peter; Zhu, Zhendong; Xedzro, Christian; Asiamah, Emmanuel; Islam, Shahidul (Frontiers in Veterinary Science, 2025)
Reproductive health is a critical determinant of livestock productivity and economic sustainability. However, it is often compromised by infectious diseases, environmental stressors, and nutritional deficits. Phytogenic extracts—bioactive compounds derived from medicinal plants—have emerged as sustainable alternatives to synthetic antibiotics and hormones, exhibiting antimicrobial, antioxidant, and immunomodulatory properties. These extracts influence key reproductive processes such as follicular development, oocyte maturation, and endometrial health while mitigating the detrimental effects of oxidative stress and pathogenic infections. Recent findings suggest that phytogenic extract can enhance reproductive performance, improve oocyte quality, and support pregnancy outcomes. Despite the growing body of evidence, optimal application strategies and the full breadth of their biological effects remain insufficiently explored. This review focuses on the molecular mechanisms modulated by phytogenic extracts, particularly in the context of hormone regulation, immune modulation, and oxidative stress mitigation. We also identify critical knowledge gaps and propose future research directions to optimize the use of phytogenic extracts as a sustainable approach to enhancing livestock reproductive health.